Identification of dopaminergic neurons of the substantia nigra pars compacta as a target of manganese accumulation12. Issue 5 (13th May 2015) - Robison, Gregory; Sullivan, Brendan; Cannon, Jason R.; Pushkar, Yulia
<x xml:space="preserve">Abstract</x> A combined approach of FluoroGold™ retrograde tracer injection and XRF imaging to perform in situ measurement of manganese content and distribution in dopaminergic cells of the rodent substantia nigra compacta.